THE EFFICIENCY OF VILLAGE GOVERNMENT SPENDING IN INDONESIA: A META-FRONTIER ANALYSIS - Tengku Munawar Chalil (Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
Introduction: This study aims to measure the efficiency of village government spending and examine the effects of village transfers (Dana Desa) and institutional properties on its efficiency. Background Problems: The village law has endowed extra grants to village governments, which questions if the villages are prepared to adequately handle large increases in funding. Novelty: While previous studies address the misappropriation in spending within the municipal dimension, this study explores the spending efficiency of the autonomous sub-municipal governments and explains the impacts of both lump-sum grants and bureaucracy factors on spending efficiency. Research Methods: This study analyzes the Indonesian 2014 Village Governments’ dataset, using the meta-cost frontier in order to measure village spending efficiency, then it probes the causal impacts of endowed fiscal transfers and bureaucratic factors on the obtained efficiency. Findings/Results: The results suggest that granting direct transfers would exacerbate the spending inefficiencies of autonomous villages. Administrative factors such as a large bureaucracy and a lack of bureaucratic capacity within the body of village governments positively affect spending inefficiencies. Conclusion: The result of this research reflects that there is a need to evaluate the village governance policy to increase spending efficiencies, specifically focusing on the adequacy of village institutions to handle village transfers.